SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA TOKO VERN KITCHEN - Raden Roro Astria Aurellia Cahyarini (2022)
One way to improve services in buying and selling activities is to create a sales information system. Many sales efforts are still lacking in terms of customer service. By using a sales information system, customers can get information and services that are easier to process transactions. The Vern Kitchen store still uses manual services that are not inputted into the system, which causes negligence in sales and transactions to customers. This design and research uses the waterfall method and uses the HTML and PHP programming languages and uses MySQL as the database. With the design of this sales information system, it can make it easier for the Vern Kitchen Store to carry out the sales process.